Higher order model of synchronous generator - Sugiarto Kadiman; Oni Yuliani (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
Synchronous generator conventional model accurately describes only the stator circuit. Concerning the transients for rotor quantities, for example rotor voltage, rotor current, and rotor magneto-motor force, conceivable predetermined with acceptable accuracy if calculations are created on equivalent model properly on consideration of field and damper together with stator circuits. Unfortunately, it was recognized that simulated responses using conventional model with calculated machine parameters often did not match well with actual measured responses, particularly in the quantity’s rotor winding. For this intention, the newly method to producing the rotor circuit is to model it as well as the lines that conventionally viewed as the partition of current paths from the physical construction. Besides the physical field and damper circuits, a third circuit for the eddy currents induced in the pole surface could also be added. The all conclusions prove the correctness of synchronous generator model.